A comparison of self‐report and discrepancy measures of camouflaging: Exploring sex differences in diagnosed autistic versus high autistic trait young adults. Issue 3 (9th December 2022) - Milner, Victoria; Colvert, Emma; Mandy, William; Happé, Francesca
Abstract: Camouflaging describes masking or compensating for autistic traits and/or related difficulties. Some evidence suggests autistic females camouflage more than autistic males, potentially contributing to delayed or missed diagnosis. Studies predominantly adopt self‐report measures of camouflaging, potentially reflecting a person's intent to camouflage without accurately measuring effectiveness (i.e., success in fulfilling the intended effect of minimizing the appearance of autistic traits) of camouflaging. Discrepancy scores between underlying cognitive difficulties (e.g., theory of mind) and observed autistic traits (henceforth camoToM ), or between self‐reported autistic traits and observed autistic traits (henceforth camoSRS ), may provide a more accurate measure of camouflaging effectiveness. Three measures of camouflaging administered to autistic males ( n  = 46) and females ( n  = 40), and adults with equally high levels of autistic traits but no diagnosis ( n  = 45 males, n  = 43 females) recruited from a large population‐based sample were compared. Self‐report measures of camouflaging were significantly correlated with camoSRS scores only. Both discrepancy scores were correlated with each other. Adults with high autistic traits, but no diagnosis, had higher discrepancy camouflaging scores than diagnosed adults, but self‐reported scores were similar. Diagnosed females scored higher than diagnosed males across all camouflaging measures, but no sex difference occurred in the high trait group. This might indicate that autistic females have higher intentions and greater effectiveness when camouflaging, compared with autistic males. For camoSRS only, high trait males scored significantly higher than diagnosed males; no group difference occurred for females. These results suggest that, despite all participants intending to camouflage to some extent, effective camouflaging as measured by discrepancy scores is higher in undiagnosed high autistic trait individuals. One interpretation is that effective camouflaging reduces the likelihood of autism diagnosis in males and females with high autistic traits. Lay Summary: Most studies use self‐report camouflaging questionnaires which measure "intention" to camouflage. One way to look at how effective a person's camouflaging is to look at the difference between autistic traits rated by another person and self‐reported autistic traits, or relevant cognitive difficulties. We used these three measures of camouflaging to look at differences between autistic males and females, and males and females without a diagnosis but with high levels of autistic traits. Our results suggest that participants in all groups report an intention to camouflage. When looking at the effectiveness of camouflaging, the participants with high traits but no diagnosis had higher scores. This suggests that effective camouflaging might make it less likely for both males and females to get an autism diagnosis. Females were also found to have higher camouflaging scores across all measures. This might indicate that autistic females have higher intentions and greater effectiveness when camouflaging, compared with autistic males.